2005
DOI: 10.1519/r-15344.1
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Different Warm-up Protocols on Fitness Performance in Children

Abstract: The purpose of this study was to compare the acute effects on youth fitness of 3 different warm-up protocols utilizing static stretching or dynamic exercise performance. Sixty children (mean age 11.3 +/- 0.7 years) performed 3 different warm-up routines in random order on nonconsecutive days. The warm-up protocols consisted of 5 minutes of walking and 5 minutes of static stretching (SS), 10 minutes of dynamic exercise (DY), or 10 minutes of dynamic exercise plus 3 drop jumps from 15-cm boxes (DYJ). Following e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 16 publications
6
46
1
4
Order By: Relevance
“…However, recent studies have showed that SS reduces muscular performance (Curry et al, 2009; Faigenbaumm et al, 2005; Behm et al, 2001; Church et al, 2001; Nelson et al, 2001), whereas other studies have reported that DS improves performance compared with SS (Herda et al, 2008; Little and Williams, 2006; Mcmillian and Moore, 2003). Many researchers have reported that DS should replace SS because of an SS-induced decrease in performance.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, recent studies have showed that SS reduces muscular performance (Curry et al, 2009; Faigenbaumm et al, 2005; Behm et al, 2001; Church et al, 2001; Nelson et al, 2001), whereas other studies have reported that DS improves performance compared with SS (Herda et al, 2008; Little and Williams, 2006; Mcmillian and Moore, 2003). Many researchers have reported that DS should replace SS because of an SS-induced decrease in performance.…”
Section: Introductionmentioning
confidence: 91%
“…Although they have demonstrated positive effects of DS, they suggested players should perform SS and DS together, for a better adaptation. Although previous studies (Amiri-Khorasani and Sotoodeh, 2013; Amiri-Khorasani et al, 2010; Faigenbaumm et al, 2005; Mikolajec et al, 2012) have investigated the combined effects of SS and DS on power, agility, and speed; however, the results were unclear about the effect of the order within each stretching combinations on fitness performances.…”
Section: Introductionmentioning
confidence: 99%
“…Faigenbaum et al 6 found that the fl exibility static affect the performance of children in a subsequent battery of tests. The negative infl uence of the warm-up in static explosive force is well documented 1,18,21 .…”
Section: Discussionmentioning
confidence: 99%
“…First, the athlete reproduces similar movements during the warm-up that he/she will use in training or in a fight, including specific rehearsal of movement before exercise (22,23,41). In addition, research suggests an advantageous increase in body temperature with dynamic stretching (23,44) when compared with static stretching, an increase in neuromuscular activity (21), stimulation of the nervous system (28,44), and an association with postactivation potentiation (21,26,36,41,44), leading to performance enhancements.…”
Section: Exercises Volumementioning
confidence: 99%